2019
DOI: 10.1186/s40635-019-0263-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of landiolol on sex-related transcriptomic changes in the myocardium during sepsis

Abstract: Objectives The aims of this study are to better understand phenotypic differences between male and female rats during sepsis, to characterise the contribution of the beta1-adrenergic blocker landiolol to septic cardiomyopathy and to determine why landiolol induces divergent effects in males and females. Methods The myocardial transcriptional profiles in male and female Wistar rats were assessed after the induction of sepsis by cecal ligation and puncture and addition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…In the second part of our study, we looked for the underlying mechanism of changes in hemodynamic pro les. We previously identi ed, in a transcriptomic study, major differences in sepsis-induced deregulation of gene expression in male and female rats and con rmed the bene t of landiolol intake on cardiac function in male (13). Our current results highlight a similar gene expression pro le in OVR females to that found in males.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In the second part of our study, we looked for the underlying mechanism of changes in hemodynamic pro les. We previously identi ed, in a transcriptomic study, major differences in sepsis-induced deregulation of gene expression in male and female rats and con rmed the bene t of landiolol intake on cardiac function in male (13). Our current results highlight a similar gene expression pro le in OVR females to that found in males.…”
Section: Discussionsupporting
confidence: 72%
“…Total RNA was isolated from the left ventricles and qPCR experiments were performed as previously described (13). Statistical Analyses Data are expressed as means ± SEM.…”
Section: In Vivo Assessment Of Vascular Permeabilitymentioning
confidence: 99%
“…In the second part of our study, we looked for the underlying mechanism of changes in hemodynamic profiles. We previously identified, in a transcriptomic study, major differences in sepsis-induced deregulation of gene expression in male and female rats and confirmed the benefit of landiolol intake on cardiac function in male 13 . Our current results highlight a similar gene expression profile in OVR females to that found in males.…”
Section: Discussionsupporting
confidence: 56%
“…Hearts, removed immediately after euthanasia, were dissected, frozen and stored at − 80 °C until analyses. Total RNA was isolated from the left ventricles and qPCR experiments were performed as previously described 13 . Primers used for trancripts detection are listed in Supplementary Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“… [117] Moreover, few studies have evaluated the impact of biological sex on SCM, [118] which has been shown to influence pathology and response to treatment in animal studies. [119] , [120] …”
Section: Limitations Of the Literaturementioning
confidence: 99%